2003
DOI: 10.1152/ajpregu.00337.2002
|View full text |Cite
|
Sign up to set email alerts
|

Responses to human CGRP, ADM, and PAMP in human thymic arteries

Abstract: . Responses to human CGRP, ADM, and PAMP in human thymic arteries. Am J Physiol Regul Integr Comp Physiol 284: R531-R537, 2003; 10.1152/ajpregu.00337.2002Responses to human CGRP, adrenomedullin (ADM), and proadrenomedullin NH2-terminal 20 peptide (PAMP) were studied in small human thymic arteries. CGRP, ADM, and PAMP produced concentrationdependent vasodilator responses in arteries preconstricted with the thromboxane mimic U-46619. Responses to ADM and PAMP were attenuated, whereas responses to CGRP were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…The most likely cascade is an ADM-NO-GABA cascade. In support of this suggestion, endothelial cells have been shown to produce and release NO in response to ADM [13,44]. In addition, our data provide anatomical support for the idea that PVN neurons can produce NO upon stimulation by ADM.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The most likely cascade is an ADM-NO-GABA cascade. In support of this suggestion, endothelial cells have been shown to produce and release NO in response to ADM [13,44]. In addition, our data provide anatomical support for the idea that PVN neurons can produce NO upon stimulation by ADM.…”
Section: Discussionsupporting
confidence: 82%
“…It has been shown that ADM activates NOS in endothelial cells of blood vessels to produce NO [13,44], and we have found that endothelial cells of blood vessels are the only endothelial NOS-positive cells in the PVN (unpublished data). Based on these data, we speculate that ADM in the PVN evokes the production and release of NO at least in part by activating endothelial NOS within the blood vessels.…”
Section: Discussionsupporting
confidence: 54%
“…cAMP has been implicated in several studies as the primary intracellular signaling molecule used by CGRP (8,13,15,23,25,37). A significant increase in cAMP following AdCMVCGRP transfection has been observed in both cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas NO is known to signal through a cGMP-protein kinase A (PKA)-p53 pathway in aortic smooth muscle (12,37), the mechanism by which CGRP elicits its beneficial effect is unknown. It is proposed that CGRP signals through a cAMP pathway (8,13,15,23,25,37). In arterial smooth muscle, vasodilator agents increase cAMP and inhibit smooth muscle proliferation by arresting the cells primarily in G 1 phase (4,39).…”
mentioning
confidence: 99%
“…If the expression of one or more of these proteins is compromised by diabetes/hyperglycemia, the function of the CGRP receptor would likely be affected. The vasodilatory response to CGRP involves the formation of cAMP and activation of Ca 2ϩ signaling pathways (1,7,18,35). It is also possible that the signaling mechanism(s) activated by the CGRP receptor may be impaired in diabetes/hyperglycemia, thereby causing a decrease in vasodilation in response to exogenous CGRP.…”
Section: Discussionmentioning
confidence: 99%